Species diversity of Cladorrhinum in Argentina and description of a new species, Cladorrhinum australe - Carmaran, Cecilia Cristina (2015)
The genus Cladorrhinum constitutes a fungal group of prime importance for agriculture and livestock, since some species have biocontrol potential or were shown to promote plant growth and to produce phytases, which are enzymes useful for processing animal feed. We assessed the species diversity of Cladorrhinum in Argentina. Strains were identified at the species level by analysis of morphological and physiological characters, as well as by using molecular characters and by sequencing three nuclear DNA loci: internal transcribed spacer regions (ITS), and the 28S ribosomal subunit and β-tubulin genes. C. bulbillosum and C. samala were detected, and a new species is described as C. australe.